Crossing frontiers: exploring the influence of global mobility on entrepreneurial innovation capabilities - Blot, Clément Félix Julien (2024)
In a world marked by increasing global mobility and accessibility of knowledge, this research identifies the significance of international experiences for entrepreneurs' innovation capabilities. This master's thesis explores the transformative impact of global mobility on entrepreneurs' innovative capacities across multiple countries. We use data derived from our 10 interviews to understand entrepreneurs' experiences from their perspectives and how global mobility has affected their capabilities to innovate. These participants were interviewed using a 16-question questionnaire established priorly. Our findings allowed the establishment of a theoretical framework for international entrepreneurs that supports our hypotheses, furthermore, the findings from our research develop an initial line of thought towards the fact that international experiences might positively contribute to entrepreneurs' innovative capabilities and opportunity recognition. This research concludes by highlighting the implications for future studies, emphasizing the need for a deeper understanding of the environmental and networking factors shaping entrepreneurial innovation in a global context.